Experiential learning, narrative‐based learning, and insurance adoption: Experimental evidence from Kenya - Osiemo, Jamleck; Cecchi, Francesco; Bulte, Erwin; Mwongera, Caroline (Wiley, 2025)
We compare the impact of two extension modalities on knowledge accumulation and willingness to pay for a weather index insurance product among smallholder farmers in Kenya. One approach to extension is based on experiential learning and involves participation in an incentivized framed experiment (or game). The other is based on conventional “narrative-based” learning. While both modalities increase farmer knowledge, incentivized gamification causes more learning. We also find that experiential learning affects follow-up demand for the insurance product, which is not true for narrative-based learning. Interestingly, demand for insurance shifts inward after playing the insurance game. This reduction in demand is mainly caused by increased knowledge about the insurance product, but we also present suggestive evidence that experiencing basis risk during the game was more salient than theory-based learning about basis risk. Game-based learning is an effective approach to promote knowledge accumulation and may accentuate or attenuate adoption of innovations by updating ex-ante, possibly biased, expectations.